Financial Literacy, Public Accountability, Information Transparency and Financial Performance Responsibility in Zakat Management at Baitul Mal Aceh Agency - Ronikeusumaranda; Hazmi, Yusri; Abdullah, Ahmad Fauzan (PT Inovasi Pratama Internasional, 2024)
This research aims to determine the influence of financial literacy, public accountability, information transparency and responsibility on the financial performance of zakat management at Baitul Mal Aceh Agency. This research uses the financial literacy variable as the main variable which is believed to have a better influence on improving financial performance. The use of financial literacy variables becomes important along with the implementation of zakat as a tax deduction as regulated by the Ministry of Finance of the Republic of Indonesia. Through financial literacy, Baitul Mal Aceh Agency can improve, especially regarding zakat management. This research also uses good governance variables, which include public accountability, information transparency and responsibility. Baitul Mal Aceh as a public sector organization is obliged to prioritize the principles of good governance in order to increase public trust in zakat management in Aceh.